CNSC-12. NEURONAL DIFFERENTIATION DRIVES THE ANTI-TUMOR EFFICACY OF MEK INHIBITION IN GLIOBLASTOMA. (14th November 2022) - Khan, Sabbir; Martinez-Ledesma, Emmanuel; Park, Soon Young; Dong, Jianwen; Piao, Yuji; Harrison, Erin; Koul, Dimpy; Balasubramaniyan, Veerakumar; de Groot, John; Yung, W K Alfred
Abstract: Multiple genomic aberrations and distinct molecular subtypes of glioblastoma (GBM) have been identified through multi-omics analyses including single-cell genomic and epigenomic analysis. Epidermal Growth Factor Receptor (EGFR ) amplification is found in nearly 50% of GBM tumors. Several EGFR inhibitors have been tested in GBM but failed to demonstrate long-term therapeutic benefit, presumably due to target heterogeneity, escape signal pathways, and acquired resistance. Therefore, we investigated downstream signaling, mitogen-activated protein kinase (MEK1/2) as a potential therapeutic target for GBM. We utilized an unbiased high-throughput screening with a panel of glioma stem-like cells (GSCs) and identified that GBM cells harboring EGFR amplification showed anti-proliferative and apoptotic cell death (sensitive) to multiple MEK inhibitors. RNA-seq analysis of cells pre- and post-treatment with trametinib, a potent MEK inhibitor, revealed an upregulation of neurogenesis and neuronal differentiation genes such as β-III tubulin, ASCL1, DLL1, DLL3, NeuroD4, PAX6 and NCAM1. In addition, downregulation of the several MEK targets including erythroblast transformation specific (ETS) family genes, particularly ETV5 was observed. We demonstrated that MEK inhibition increased neuronal differentiation demonstrated by immunofluorescence, western blot, and RT-qPCR experiments using selected differentiation markers (β-III tubulin, ASCL1, DLL3, and NeuroD4). In addition, ETV-5 knockout in GSCs by CRISPR/Cas-9 promoted the expression of neuronal differentiation genes. Oral treatment of trametinib in an orthotopic GSC xenograft model significantly improved animal survival, in which 25-30% of mice are long-term survivors. This was accompanied by decreased MEK/ERK signal and cell proliferation in tumor tissues. Thus, we demonstrated here that MEK1/2 inhibition by trametinib induces neuronal differentiation mediated through downregulation of ETV-5 in GBM, a potential novel mechanism of action of MEK1/2 signal inhibition.